2019
DOI: 10.1088/1757-899x/541/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene oxide from used electrode graphite with controlled oxidation process

Abstract: Graphene oxide and reduced graphene oxide attract a lot of attention due to graphene provides some properties that suitable for wider application. Properties of graphene are unique since it can be tuned regarding to its controlled synthesis method and several treatments. This work, graphene oxide was synthesized from used graphite electrode by modified Hummer’s method in which oxidation process controlled. Zinc was used to produce reduced graphene oxide. Graphene oxide and reduced graphene oxide were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Despite the sulfur residue, manganese and nitrogen impurities were not detected in the synthesized GO (Fig. 5e and f) 65,66 . The elemental analysis by XPS revealed that the contents of carbon, oxygen, and sulfur were 65.9, 33.6, and 0.4 at%, respectively.…”
Section: Characteristics Of Go From Modified Hummers' Methodsmentioning
confidence: 97%
“…Despite the sulfur residue, manganese and nitrogen impurities were not detected in the synthesized GO (Fig. 5e and f) 65,66 . The elemental analysis by XPS revealed that the contents of carbon, oxygen, and sulfur were 65.9, 33.6, and 0.4 at%, respectively.…”
Section: Characteristics Of Go From Modified Hummers' Methodsmentioning
confidence: 97%
“…Among them, 1449 cm −1 is the torsional vibration of the−OH bond, and 1380 cm −1 is the stretching vibration of C− O. 24,25 This indicates that the oxidation treatment successfully generated many oxygen-containing groups on the MWCNTs. Comparison between the O-MWCNTs and the rest of the samples showed that the loading of Pt resulted in a decrease in the peak intensity of the oxygen-containing groups.…”
Section: Structural and Morphological Characterization Of Catalystsmentioning
confidence: 98%
“…rGO derived from spent coffee grounds has been reported as electrode material for RFBs [61]. The coffee grounds were washed and dried, then were carbonized at 850 • C in nitrogen for 2 (rGO-2) or 3 h (rGO-3), chemically activated via modified Hummer's method to prepare GO [62], then reduced by hydrazine monohydrate reduction to produce rGO [63], obtaining BET surface areas of 72 m 2 g −1 for both rGO-2 and rGO-3. The rGO-3 sample presented 1% more O and rGO-2 1% more N determined by XPS, indicating higher reduction in the case of rGO-2.…”
Section: Boosting Activity Of Carbon Felts Via Decoration With Biomas...mentioning
confidence: 99%